Cone Beam Computed Tomography Evaluation of Socket Healing After Third Molar Germ Extraction: A Case Series Study Including Adolescents with Osteogenesis Imperfecta Type I Treated with Bisphosphonates and Healthy Age-Matched Subjects - Giacomo D’Angeli; Francesca Zara; Francesca Arienzo; Daniela Messineo; Mauro Celli; Gian Luca Sfasciotti; Iole Vozza; Mara Riminucci; Antonella Polimeni; Alessandro Corsi (Applied Sciences)
Bisphophonates (BPs) are widely used in Osteogenesis imperfecta (OI). Cone Beam Computed Tomography (CBCT) shows clinical usefulness in evaluating impacted teeth and adjacent structure relationships, extraction socket healing, bone mineral density (BMD) and BP-related jaw osteonecrosis (BRONJ). The aim of the study was to compare alveolar sockets and the adjacent bone area before and after third molar extraction in OI type I (OI-I) adolescents treated with BPs and age-matched healthy subjects (HSs) by CBCT. Methods: Five adolescents with genetically proven OI-I treated with BPs (three males and two females, mean age: 15.2 ± 1.78 years) and four age-matched healthy subjects (two males and two females, mean age: 15.5 ± 1.29 years) were included in this study. Eight Regions of Interest (ROIs) were evaluated: between 3.7 and 3.8 (ROI-1) and 4.7 and 4.8 (ROI-2); after 3.8 (ROI-3) and 4.8 (ROI-4); alveolar sockets 3.8 (ROI-5) and 4.8 (ROI-6); left (ROI-7) and right (ROI-8) cortical bone. Results: ROIs were evaluated on both sides of the mandible for all the subjects except one OI patient in which CBCTs were performed pre- and-post third molar extraction only on the right side. CBCT was performed 12.8 ± 4.60 and 11.5 ± 2.51 days before and 8.0 ± 1.41 and 7.7 ± 0.5 months after extraction in OI-I and HSs, respectively. BPs were discontinued 62.0 ± 36.5 months before extraction. None of the OI-I adolescents developed BRONJ. Statistically significant greater values were observed in OI-I for ROI-1 and -2 (p = 0.0464), ROI-3 and -4 (p = 0.0037) and ROI-7 and -8 (p = 0.0079) after extraction. Conclusions: This descriptive study confirms that, in OI-I adolescents treated with BPs, third molar extraction is safe, and socket healing occurs properly. In addition, it demonstrates that, if the same device and imaging conditions are used and comparisons to predetermined standard values are avoided, CBCT can be used to monitor BMD changes. The significant greater BMD observed for different ROIs in OI-I could reflect the increased secondary mineralization related to the BP-dependent reduction in bone turnover.